Comparison of two techniques in proximal anastomosis in acute type A aortic dissection - Fang, Changcun; Gao, Shan; Ren, Xiao; Pang, Xinyan; Zhao, Xin; Ma, Zengshan; Wang, Chen; Liu, Kai (Frontiers in Cardiovascular Medicine, 2022)
Background The proximal anastomosis is an important procedure during the acute type A aortic dissection (AAAD) surgery. The conventional method is a double patch sandwich technique with Teflon felt. Adventitial eversion and prosthesis eversion technique as a novel approach has been applied to many patients in our center. Herein, This technique would be introduced, and the perioperative and 1-year follow-up results of the two different anastomosis methods were also evaluated. Methods Between December 2017 and May 2021, 143 AAAD patients who underwent total arch replacement (TAR) and frozen elephant trunk (FET) implantation were included in this retrospective study. Patients were divided into the eversion technique group (adventitial eversion and prosthesis eversion technique for proximal anastomosis, n = 64) and the sandwich technique group (n = 79). Results The medical records were analyzed and compared between the groups. The mean operation time was 466 ± 73 min in the eversion technique group and 513 ± 81 min in the sandwich technique group (P < 0.001). Compared with the sandwich technique group, the eversion technique group also showed a shorter time on proximal anastomosis (38 ± 12 min vs. 58 ± 20 min, P < 0.001), cardiopulmonary bypass (195 ± 26 vs. 211 ± 40 min, P = 0.003), and aortic cross-clamp (120 ± 23 min vs. 134 ± 27 min, P = 0.002). Furthermore, a decreased proportion of >600 ml fresh frozen plasmas transfusion was observed in eversion technique group (10.9% vs. 34.2%, P = 0.002). No statistical differences were found in the postoperative morbidities and 1-year follow-up outcomes. Conclusion Proximal anastomosis with adventitial eversion and prosthesis eversion technique is a promising surgical option for AAAD patients, with favorable perioperative and 1-year follow-up results.